The role of the autonomic ganglia in atrial fibrillation - Stavrakis, Stavros (JACC Clin Electrophysiol, 2015)
Recent experimental and clinical studies have shown that the epicardial autonomic ganglia play an important role in the initiation and maintenance of atrial fibrillation (AF). In this review, we present the current data on the role of the autonomic ganglia in the pathogenesis of AF and discuss potential therapeutic implications. Experimental studies have demonstrated that acute autonomic remodeling may play a crucial role in AF maintenance in the very early stages. The benefit of adding ablation of the autonomic ganglia to the standard pulmonary vein (PV) isolation procedure for patients with paroxysmal AF is supported by both experimental and clinical data. The interruption of axons from these hyperactive autonomic ganglia to the PV myocardial sleeves may be an important factor in the success of PV isolation procedures. The vagus nerve exerts an inhibitory control over the autonomic ganglia and attenuation or loss of this control may allow these ganglia to become hyperactive. Autonomic neuromodulation using low-level vagus nerve stimulation inhibits the activity of the autonomic ganglia and reverses acute electrical atrial remodeling during rapid atrial pacing and may provide an alternative non-ablative approach for the treatment of AF, especially in the early stages. This notion is supported by a preliminary human study. Further studies are warranted to confirm these findings.